Surface molecularly imprinted solid-phase extraction for the determination of vancomycin and norvancomycin in milk by liquid chromatography coupled to tandem mass spectrometry. (1st February 2022) - Zhou, Hao; Liu, Rong; Chen, Qianqian; Zheng, Xiantong; Qiu, Jingli; Ding, Tongyan; He, Limin
Highlights: Teicoplanin-imprinted polymers for purifying vancomycin and norvancomycin in milk. A LC–MS/MS method was established for the determination of residues of two analytes. Mean recoveries for vancomycin and norvancomycin were from 83.3% to 92.1%. The limit of detection of vancomycin and norvancomycin were 0.5 μg/kg. Abstract: A simple and sensitive method based on surface molecularly imprinted solid-phase extraction (SMISPE) combined with liquid chromatography-tandem mass spectrometry (LC–MS/MS) was developed to determine the residues of vancomycin (VCM) and norvancomycin (NVCM) in milk samples. The imprinted polymer prepared with teicoplanin as a virtual template can specifically recognize VCM and NVCM. The samples were purified with SMISPE and analyzed by LC–MS/MS in positive ionization mode. The results showed that the VCM and NVCM had a good linear correlation in the range of 0.5 μg/kg to 50 μg/kg. The recoveries of target analytes were from 83.3% to 92.1%, and the limits of quantification were both 1.0 μg/kg. The matrix effects of VCM and NVCM were −11.0% and −3.43%, respectively. The proposed method can efficiently eliminate the interference from matrix compounds and reduce baseline noise, which is useful for the monitoring of the residues of VCM and NVCM in milk samples.